From Expectation to Action: The Interplay of Health Expectations, Care Quality, and Socio-demographic Moderators in Health-Seeking Behaviour of Health workers (Journal of Management and Social Sciences, 2025)
Health-seeking behaviour among health workers is a crucial yet often overlooked aspect of healthcare systems, especially in developing nations. This study investigates the impact of health expectations and perceived health care quality on health-seeking behaviour (HSB) among Nigerian health workers. A cross-sectional survey was conducted among 108 health workers in Ibadan, Nigeria. Structural equation modelling (SEM) was used to assess the relationships between health expectations and health-seeking behaviour (HSB). Health expectations positively predicted perceived health care quality (β = 0.410, p < .001) and HSB (β = 0.268, p = .003). Perceived care quality strongly influenced HSB (β = 0.652, p < .001) and mediated the relationship between health expectations and HSB (β = 0.267, p < .001). Age moderated the effect of health expectations on HSB (β = 0.366, p = .003), indicating a stronger association among older health workers. Ethnicity moderated the relationship between care quality and HSB (β = 0.211, p = .038), while marital status moderated the link between health expectations and HSB (β = -0.320, p < .001). The model demonstrated acceptable fit indices: SRMR = 0.072, NFI = 0.915, and Rms theta = 0.102, indicating a good fit between the hypothesized model and the observed data. The findings underscore the significant roles of health expectations and perceived care quality in shaping HSB among health workers, with socio-demographic factors influencing these dynamics. Tailored interventions that enhance care quality and consider individual expectations and demographic contexts are essential to promote proactive health-seeking behaviours within the health workforce.KeywordsHealth expectations, care quality, socio-demographic factors, health-seeking behaviour, health workers